2015
DOI: 10.3928/01484834-20150218-02
|View full text |Cite
|
Sign up to set email alerts
|

“Why Can’t I Pass These Exams?”: Providing Individualized Feedback for Nursing Students

Abstract: The nursing literature on examination remediation and testing feedback strategies focuses primarily on NCLEX-RN success and remediation, rather than on the course examinations taken by students throughout program curricula. Students deemed at risk for NCLEX-RN failure likely have displayed poor performance on examinations long before graduation and licensure testing. Individualized examination feedback that identifies students' specific weaknesses is superior to correct answer feedback. The feedback grid descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In her research, Hadenfeldt (2012) found similar findings; 86 percent of students with individualized improvement plans completed the nursing program. Just as this QI study demonstrated statistically significant exam score improvement upon initiation of remediation, Wiles (2015) also described improvement in student scores and nursing program completion after initiating individualized examination review or improvement plans. Students in the Wiles study found the benefits of individualized feedback and faculty-initiated interactions helpful, as did the students in our study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In her research, Hadenfeldt (2012) found similar findings; 86 percent of students with individualized improvement plans completed the nursing program. Just as this QI study demonstrated statistically significant exam score improvement upon initiation of remediation, Wiles (2015) also described improvement in student scores and nursing program completion after initiating individualized examination review or improvement plans. Students in the Wiles study found the benefits of individualized feedback and faculty-initiated interactions helpful, as did the students in our study.…”
Section: Discussionmentioning
confidence: 63%
“…Elkins (2015) examined strategies for increasing student retention, including early identification of students at high risk for failure and the implementation of interventions designed to promote student success. Individualized remediation was identified by Wiles (2015) as a key method to support student success. Exam score for students who met with faculty for an individualized examination review increased an average of 9.6 points (range: 1 to 21).…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was also observed in another study involving a nursing program. 10 Both underscore students' inherent motivation to improve on their own once they realize the existence of a deficiency. Therefore, bringing the deficiency to the students' attention plays a critical role in their self-driven improvement.…”
Section: Discussionmentioning
confidence: 99%
“…9 In a 2015 article, Wiles described an individualized, faculty-facilitated examination feedback procedure, which improved student performance by identifying students' specific weaknesses. 10 The procedure involved the use of a so-called "feedback grid" that allowed the faculty member to identify specific weaknesses of a particular student among various areas, including content-specific knowledge, comprehension, application, analysis, synthesis and evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal feedback not only provides individuals with the correct answer but also offers an explanation as to why the answer is correct. [51][52][53] Generally speaking, the more detailed the feedback, the greater the TEL effects.…”
Section: Best Practices In Test-enhanced Learningmentioning
confidence: 99%